Peranan Kepemimpinan, Disiplin Kerja dan Budaya Organisasi Terhadap Motivasi dan Kinerja Pegawai Kantor Kelurahan di Kecamatan Jebres, Kota Surakarta - Sayuti, Retno; Awatara, I Gusti Putu Diva (Nur Science Institute, 2023)
This study aims to analyze and determine the role of Leadership, Work Discipline and Organizational Culture on Employee Performance with Motivation as an Intervening Variable at Kelurahan employees in Jebres District, Surakarta City. The data collected in this study was done by distributing questionnaires. This research uses the method of analysis of reliability test and validity test, path analysis, t test, F test, and the coefficient of determination test (R2) and Sobel test. The specimens in this research are civil servants in the Kelurahan in Jebres District, Surakarta City, with a total of 35 people using the census/population technique. The results of the t-test of the first equation show that leadership has a positive and insignificant effect on motivation, discipline has a positive and significant effect on motivation and organizational culture has a negative and insignificant effect on motivation. The t-test in the second equation shows that leadership and motivation have a positive and significant effect on performance, while discipline and organizational culture have a positive and insignificant effect on performance. Based on the results of tests carried out simultaneously (Test F) shows that together the independent variables of leadership, discipline, and organizational culture affect performance with motivation as an intervening variable. The total R2 value obtained is 0.765 (76.5%). The results of the path analysis show that the recommended effort is to maintain leadership behavior and motivation to improve the performance of Kelurahan employees in Jebres District, Surakarta City.